1995
DOI: 10.1111/j.1365-2095.1995.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring feeding behaviour and food intake: methods and applications

Abstract: There are three main methods used in the study of feeding behaviour and food consumption in captive populations of fish. These are direct observation, the recording of feeding activity using 'on-demand' feeders, and the quantitative determination of gastrointestinal content using a non-invasive 'labelled feed' technique. Observational techniques have been widely used in studies of foraging behaviour and feeding responses, but these methods are usually confined to the study of fish held in small groups. 'Labell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 79 publications
3
39
0
1
Order By: Relevance
“…1995) or radioisotopic methods (Storebakken et al . 1981; Jobling et al . 1995) have also been used for comparison of the palatability of food materials for fish.…”
Section: Methods In Studies Of Fish Taste Preferencesmentioning
confidence: 99%
“…1995) or radioisotopic methods (Storebakken et al . 1981; Jobling et al . 1995) have also been used for comparison of the palatability of food materials for fish.…”
Section: Methods In Studies Of Fish Taste Preferencesmentioning
confidence: 99%
“…In their studies, treatments receiving a ration of 3-4% BW/day showed no significant difference in total body weight gain and SGR compared with treatment with 2% BW per day, suggesting that conversion efficiency may be metabolically limited. Jobling et al (1995) reported that feeding below an optimum rate in each feeding interval to reach satiation can result in higher competition with subsequently higher energy expenditure, followed by differences in feeding utilization and finally heterogeneous fish growth.…”
Section: Itemsmentioning
confidence: 98%
“…Addition of electrolytic iron appeared to have no effect on time for food passage; the first faeces appeared at similar times to iron-free food. Barium sulphate was found to be an unsuitable marker because it had to be used in such high concentrations that it made the meal unpalatable (Edwards, 1971;Jobling et al, 1995). Ballotini lead glass beads have been used previously to measure food uptake in lobsters (Thomas et al, 2002).…”
Section: Discussionmentioning
confidence: 99%